Pengelompokkan Daerah Rawan Demam Berdarah (DBD) di Jawa Timur Menggunakan Metode K-Means - Auditiyah, Cellyn (ESTIMASI: Journal of Statistics and Its Application, 2024)
Tropical diseases are common in areas with tropical and subtropical climates. As a country with a tropical climate, Indonesia is vulnerable to various tropical diseases. A large number of tropical diseases can occur in the temperate climate zone, differing only in the frequency with which they are affected. Dengue hemorrhagic fever is a tropical disease in Indonesia. DHF occurs as a result of infection with the dengue virus which is transmitted through the bite of the female Aedes aegypti mosquito. The high prevalence of DHF in East Java requires a data collection process to identify areas that are frequently infected with DHF. Therefore, we need a clustering system that can help classify areas that often experience DHF cases. This study aims to find out which districts/cities have the predominant cases of dengue fever. The clustering method used is K-Means clustering. Based on the research conducted, 2 clusters were obtained with a silhouette coefficient  value of 0.76. Cluster 1 covers 36 districts/cities and is an area with a low level of vulnerability to dengue fever, while cluster 2 covers 2 districts/cities and is an area with a high level of vulnerability to dengue fever.